Thlaspi arvense suppresses gut microbiota related TNF inflammatory pathway to alleviates ulcerative colitis - Wang, Wenkai; Zhao, Yiyang; Wang, Ziwei; Wang, Chaowei; Bi, Ling; Wang, Yan (Frontiers in Immunology, 2025)
IntroductionThlaspi arvense (TA), commonly known as “Ximi” or “Subaijiang,” is a traditional Chinese medicinal herb used to prevent and treat ulcerative colitis (UC). However, the precise mechanisms underlying its therapeutic effects remain unclear, necessitating further investigation to identify potential pharmaceutical applications for UC management. This study aims to elucidate the efficacy and mechanisms of TA and its active constituents in UC treatment.MethodsThis study first evaluated the effects of varying TA doses on 3% dextran sulfate sodium (DSS)-induced UC. Gut microbiota alterations in UC mice were analyzed via 16S rRNA sequencing, with correlation analyses to reveal the relationship between gut microbiota and cytokines. Then, network pharmacology was utilized to identified potential TA targets for UC treatment. Protein-protein interaction (PPI) networks, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were employed to explore TA’s mechanisms. Molecular docking and dynamics simulations validated interactions between TA’s active compounds and UC-related targets. Finally, TNF pathway modulation by TA and its active component, isovitexin, was verified in vitro and in vivo.ResultsTA alleviated DSS-induced weight loss in a dose-dependent manner, reduced disease activity indices, and preserved intestinal mucosal barrier integrity. Subsequently, fluorescence in situ hybridization (FISH) revealed TA suppressed microbial translocation in intestinal tissues. To further characterize inflammatory responses, ELISA demonstrated that TA modulated levels of key cytokines (TNF-α, IL-1β, IL-6, IL-10) and oxidative stress markers (SOD, MDA), indicating systemic anti-inflammatory effects. Building on these findings, 16S rRNA sequencing analyses showed that TA regulated gut microbiota alpha/beta diversity and inhibited infectious disease-related pathways. Notably, correlation heatmaps highlighted a strong association between TNF-α levels and Escherichia-Shigella abundance, with high-dose TA significantly reducing this pathogenic bacterial genus. To systematically explore molecular mechanisms, network pharmacology identified 220 potential TA targets for UC treatment. Consistent with experimental data, PPI and KEGG analyses implicated TNF-α, IL-6, and AKT as key targets, primarily through TNF signaling pathway modulation. To validate these predictions, molecular docking confirmed stable interactions between TA compounds and identified targets, while dynamics simulations specifically emphasized isovitexin’s high affinity for TNF-α. Finally, experiments in vivo demonstrated TA’s inhibition of TNF-α-mediated NF-κB pathway activation, and in vitro studies confirmed that isovitexin directly mitigated TNF-α-induced intestinal epithelial damage. Furthermore, TA demonstrated potent inhibition of TNF-α-mediated NF-κB inflammatory pathway activation in intestinal tissues, while its active constituent isovitexin effectively mitigated TNF-α-induced epithelial cell damage, collectively highlighting their complementary anti-inflammatory mechanisms.DiscussionCollectively, Thlaspi arvense (TA) ameliorates ulcerative colitis through synergistic mechanisms involving gut microbiota modulation, inflammatory pathway suppression, and intestinal barrier preservation. By remodeling microbial communities to reduce Escherichia-Shigella colonization and microbial translocation. TA concurrently inhibits TNF-α/NF-κB-driven inflammation, and oxidative stress regulation. Furthermore, its active constituent isovitexin directly attenuates TNF-α-induced epithelial damage, demonstrating multi-scale therapeutic efficacy. These findings establish TA’s multi-target pharmacology spanning host-microbe interactions and intracellular signaling, while providing a rationale for standardizing TA-based formulations and advancing isovitexin as a precision therapeutic agent for inflammatory bowel diseases.